ТҮРКІ ТІЛДЕРІНДЕГІ МОДАЛЬ СӨЗДЕР. - Молгаждаров, Қ. (Journal of Oriental Studies, 2016)
В статье рассматриваются исследования модальныхслов тюркских языков и дается пояснение обисторическом составе.Investigation of modal verbs of the Turkish languagesis discussed in the article and explanation of historicalcomposition is given